(untitled) (Revista de Ensino em Artes, Moda e Design, 2022)
Many are the starting points for the construction of a garment piece. For instance, pattern making books and magazines, fashion periodicals, or the garment itself may be used as reference. With the advent of the internet, there was an enlargement of reference sources, such as blogs, video tutorials and the facilitated access to foreign materials, especially in English. This article presents a reflection on the possibilities of definition and translation of technical words commonly used in the field of garment pattern making and sewing. Pattern making books in English from the authors Armstrong (2010), Cole (2016) and Richardson (2008) were used as reference and it had as comparative basis, the pattern making book from Berg (2019), in Portuguese. It is presented a study on six terms (across chest, across back, back neck, back neckline, squared-off angle e marcel stitch), which stood out from the reflexions made. To conclude, it is discussed, briefly, the possibility of elaboration of a consultation material, such as a glossary of terms in English-Portuguese, aiming to facilitate further research in the field of garment pattern making in general.